Розсіяння світла на шорсткій поверхні кварцу синусоїдальної форми, покритої тонким шаром золота - Grigoruk, V. I.; Kanevskii, V. I.; Kolenov, S. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2019)
Calculation of light scattering by rough quartz surface covered with the gold film is shown. 2D vector Helmholtz equation solved using finite element approach is proposed. The interface between quartz and gold film is chosen as a surface which has sine wave form. It is shown that if using the surface highlight from the side of the quartz (complete internal reflection of light is required) and rms of rough gold thin film surface is insignificant ( nm) then (a) energy streams, caused the falling wave, are substantially disturbed near-by this surface only, (b) the crest of falling wave changes own position depending on the phase of the wave, (c) the size of the given wave crest in the rough surface peak is higher than the one in the valley, (d) the energy of the wave which dissipates on a thin film of gold in the far scattering zone is much smaller than the energy of the incident wave, (e) the contrast of quartz rough surface diminishes when its correlation length increases, (f) the contrast is practically independent of the length of the incident wave in the case where the conditions for the existence of a surface plasmon resonance are not fulfilled.